Inhibition of epidermal growth factor receptor stimulates prolactin expression in primary culture of the mouse pituitary gland. (8th July 2019) - Nogami, Haruo; Koshida, Ryusuke; Omori, Hiroyuki; Shibata, Masahiro; Harigaya, Toshio; Takei, Yosuke
Abstract: The roles of epidermal growth factor (EGF) in the regulation of prolactin (PRL) gene expression in the normal pituitary gland remain poorly understood. In the present study, the effects of EGF and an inhibitor of the EGF receptor, erlotinib, on PRL gene expression were examined both in the pituitary tumour cell line GH3 and in a primary culture of the mouse pituitary gland under similar experimental conditions. The results showed that EGF stimulated PRL expression in GH3 cells, but not in normal cells. Erlotinib was found to counteract EGF in GH3 cells inhibiting the PRL expression enhanced by EGF. By contrast, erlotinib induced an elevation in the PRL mRNA levels in the primary culture of the adult pituitary gland and the initiation of PRL production in the culture of the foetal pituitary gland in which PRL production had not yet occurred. Western blot analyses showed that EGF induced and erlotinib inhibited the activation of extracellular regulated protein kinase equally in GH3 and normal cells. These results suggest that the consequences of EGF receptor activation in normal PRL cells contradict those in adenomatous PRL cells.